Carbon premium versus non-carbon premium: Case of the Korean stock market - Lee, Kangil (Edelweiss Applied Science and Technology, 2025)
This study analyzes how the implementation of emissions trading affects the Korean stock market. The South Korean government initiated greenhouse gas (GHG) emissions trading in 2015. Primarily, the scheme increases the cost for carbon emitters. Hence, a stock market investor may be disinclined to invest in the stocks of carbon polluters. However, over-allocation caused a ‘windfall profits’ problem in the early period of the EU-ETS. Higher cash flows from windfall profits and carbon risk would bring a ‘carbon premium.’ That is, carbon risk has an ambivalent impact on the stock market. Consequently, we cannot ascertain which effect has a greater influence on the financial market unless we comprehensively analyze the Korean situation. We used panel fixed-effects models and quasi-experimental methods to examine the impact of emissions trading on the stock market, using monthly data from South Korean companies listed on the KRX300. The results indicate that introducing carbon regulations rendered carbon-emitting firms less attractive to South Korean stock market investors. Reversal consequences in several periods were represented due to institutional issues, which were mainly allocation matters and banking restrictions in Korean emissions trading. This finding suggests that the Korean asset market reacts effectively to GHG regulation.